2015
DOI: 10.14444/2035
|View full text |Cite
|
Sign up to set email alerts
|

Fine grained osseointegrative coating improves biocompatibility of PEEK in heterotopic sheep model

Abstract: Coating of PEEK dowels with a nanocoating of titanium has beneficial effects on adhesion of bone tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…There indeed is an abundance of research that demonstrated the enhanced osseointegration of Ti coatings, 11,15,18,19 and CaP coatings. 17,45 In contrast, there are only a limited number of clinical studies that explored the use of coated PEEK cages. 15 To the best of our knowledge, there are no clinical studies that explored the use of PEEK cages with a CaP coating in PLIF.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There indeed is an abundance of research that demonstrated the enhanced osseointegration of Ti coatings, 11,15,18,19 and CaP coatings. 17,45 In contrast, there are only a limited number of clinical studies that explored the use of coated PEEK cages. 15 To the best of our knowledge, there are no clinical studies that explored the use of PEEK cages with a CaP coating in PLIF.…”
Section: Discussionmentioning
confidence: 99%
“…11 There indeed is a surging research interest to enhance the osseointegration of PEEK cages by applying surface treatments and/ or coatings. 8,11,15,[17][18][19][20] Various types of bioactive coatings have been developed to improve upon the limited osseointegration of PEEK, for example, calcium phosphate (CaP), 13,17 hydroxyapatite (HA), 8,11 carbon coatings, 21 and Ti. 8,11,15,18,19 The biological impact of all these coatings has been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations